1996
DOI: 10.1038/bjc.1996.243
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability and pharmacokinetics of oral topotecan: a new topoisomerase I inhibitor

Abstract: Summary The results of preclinical and clinical studies indicate enhanced antineoplastic activity of topotecan (SKF 104864-A) when administered as a chronic treatment. We determined the apparent bioavailability and pharmacokinetics of topotecan administered orally to 12 patients with solid tumours in a two-part crossover study. The oral dose of 1.5 mg m 2 was administered as a drinking solution of 200 ml on day 1. The i.v. dose of 1.5 mg m-2 was administered as a 30 min continuous infusion on day 2. The bioava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
50
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 114 publications
(56 citation statements)
references
References 14 publications
6
50
0
Order By: Relevance
“…The absolute bioavailability of topotecan averaged 42%, which is in good agreement with previous reports (Eckardt et al, 1995;Schellens et al, 1996). The bioavailability of topotecan calculated using only the lactone data was 38%.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The absolute bioavailability of topotecan averaged 42%, which is in good agreement with previous reports (Eckardt et al, 1995;Schellens et al, 1996). The bioavailability of topotecan calculated using only the lactone data was 38%.…”
Section: Discussionsupporting
confidence: 81%
“…In previous studies, bioavailability of the i.v. formulation of topotecan administered orally was 30-44% with moderate interpatient variability (Eckardt et al, 1995;Schellens et al, 1996). A phase I study of a gelatin capsule formulation of topotecan has determined the MTD to be 2.3 mg m -2 for the daily times five dosing schedule (Gerrits et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, in humans the absolute bioavailability averaged 11.3 ± 5.2%. In comparison, bioavailability studies of topotecan showed a variable systemic exposure of 32% and 44%, which is higher than the bioavailability of oral GI147211 (Kuhn et al, 1995;Schellens et al, 1996). The bioavailability after oral administration of GI14721 1 showed wide interpatient variability ranging from 4.8% to 24.3%.…”
Section: Discussionmentioning
confidence: 97%
“…The bioavailability of oral TPT varies from 32% to 44% with relatively limited intrapatient variation (Kuhn et al, 1995;Schellens et al, 1996). Oral TPT was studied in paediatric patients with solid tumours in a phase I study with two different dose schedules.…”
Section: Prolonged Exposurementioning
confidence: 99%